Calidad del agua en la Quebrada Salitral, La Guácima, Alajuela - Salgado, Viviana (1999)
Salgado, V. (1999). Calidad del agua en la Quebrada Salitral, La Guácima, Alajuela. [Tesis de Licenciatura]. Universidad Nacional, Costa Rica.